Relevansi Ajaran Kepemimpinan Belandaskan Filosofis Asta Bratha di Era Milenial - Ayu Febrianti Akbar (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2022)
Leadership is an important part in all areas of life to achieve goals. The reality is that there is often a crisis of public trust in leaders. With the discovery of many cases that seem inappropriate and ethical by leaders and the rise of current leadership practices that adopt leadership models from outside. Meanwhile, the leader who is expected from the perspective of the millennial generation is to have the ability, intellectuality, integrity, honesty and vision that is far ahead in line with the progress of the times and is able to apply the values of local wisdom. Efforts to overcome leadership problems in the millennial era require directed and concrete actions. One of them is by exploring the philosophy of Javanese leadership based on local wisdom. the current leader had jumped too far from his essence footing. Asta Brata is symbolized by eight natural characters or can be interpreted as eight conditions that must be held by a leader. Mastery of these eight characteristics is the most ideal and appropriate leadership trait to be applied. The purpose is to find out the relevance of Asta Bratha's teachings in the millennial era. This type of research is library research. The data collection method used is the documentation method. Conclusion of the concept of leadership based on the philosophy of Asta Bratha Presenting ideal leadership for millennials